Manusia dalam Perspektif Pendidikan Islam: Telaah Konseptual Tafsir Tarbawi - Subir, Muh. Syuhada; Islam, Muhammad Thoriqul; Darmawan, Luqi; Azmi, M. Ulul; Mushaffa, Arju (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Humans are creatures who are given intellect, lust, and thought, so to humanize humans it is necessary to have guidelines or references, namely through education. With education, life will be more oriented towards the goals that they want to achieve. The research aims to comprehensively describe human understanding of its relevance to education as the main means for humans. This article is the result of literature (library) and Descriptive Analysis using existing evidence books. The research method used is Library Research to solve a problem. This research was conducted by examining literature data in depth, both secondary and primary. The results of the analysis found that human beings will not be separated from the corridors that have been determined by the code of ethics in education based on the Qur'an and As-Sunnah, Ijma and Qiyas, on their journey. And in the end man will always be obedient and obedient. 'Contrary to the command of the holy spirit as the god of the universe, so that the meaning of Human Beings and their Relevance to Education is to create human beings with noble character and have knowledge that is balanced with the development of the times.